Melanin in a changing world: brown trout coloration reflects alternative reproductive strategies in variable environments. (12th August 2017) - Jacquin, Lisa; Gauthey, Zoé; Roussille, Vincent; Le Hénaff, Michel; Tentelier, Cédric; Labonne, Jacques
Abstract : Melanins are the most widespread pigments in animals but their adaptive significance remains elusive. Using an experimental approach, we showed that darker males of brown trout had a higher reproductive investment, but a lower reproductive success than paler males in variable water flows. Since climate change will lead to an increased variability in river flows in the next decades, this suggests that darker fish might be at higher risk than their paler counterparts. Abstract: Melanins are the most widespread pigments in animals but their adaptive significance remains elusive. Recent studies suggest that intraspecific variation in melanin-based coloration reflects individual genetic-based alternative strategies to cope with environment variability, which could be crucial for their responses to climate changes. However, empirical evidence is still scarce. In this study, we tested how skin coloration in natural populations of brown trout S almo trutta fario would reflect alternative reproductive strategies in different environments. We experimentally manipulated the flow regime (constant vs. variable) in artificial streams and compared the reproductive investment (body mass and plasma triglyceride variations), innate immunity (variations in plasma peroxidase and lysozyme activity) and reproductive success (number of mates and offspring) of differently colored brown trout over 2 reproductive seasons. Results show that darker males had a higher reproductive investment, but similar immune variations during reproduction compared to paler males. In addition, this reproductive investment was higher in variable environments. However, this did not translate into a higher reproductive success in variable environments, as darker males had a similar number of mates and offspring compared to their paler counterparts under a variable water flow. Since climate change will likely lead to an increased flow variability in the next decades, this suggests that darker brown trout could incur a higher energetic cost of reproduction and could be more impacted by climate changes than their paler counterparts. This highlights the need to take into account intraspecific variability to better forecast the response of natural populations to climate changes.